2006
DOI: 10.1080/13504850500400637
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign direct investment affect domestic income inequality?

Abstract: Using pooled Gini coefficient 1993 to 2002 data for 119 countries from World Development Indicators 2004, World Bank, we find that income inequality, defined as the Gini coefficient, increases as FDI stocks as a percentage of GDP increase. Increases in per capita GDP and real per capita GDP growth rate reduce income inequality in a country, whereas an increase in GDP deteriorates income distribution. Furthermore, Latin American and Caribbean countries proved to have a less equal income distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 10 publications
5
103
2
11
Order By: Relevance
“…Many studies estimating the relationship between fdi and income inequality have found it to be positive (Tsai, 1995;Velde, 2003;Choi, 2006;Basu and Guariglia, 2007;Herzer, Hühne and Nunnenkamp, 2012), while others have found it to be negative, or have been unable to find any relationship (Milanovic, 2003;Sylwester, 2005). At the microeconomic level, however, a large branch of the literature has found that when fdi is present, the wage gap between skilled and unskilled workers increases, as therefore does income inequality (Lipsey and Sjöholm, 2004;Mah, 2002;Velde, 2003;Aitken, Harrison and Lipsey, 1996;Feenstra and Hanson, 1997).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Many studies estimating the relationship between fdi and income inequality have found it to be positive (Tsai, 1995;Velde, 2003;Choi, 2006;Basu and Guariglia, 2007;Herzer, Hühne and Nunnenkamp, 2012), while others have found it to be negative, or have been unable to find any relationship (Milanovic, 2003;Sylwester, 2005). At the microeconomic level, however, a large branch of the literature has found that when fdi is present, the wage gap between skilled and unskilled workers increases, as therefore does income inequality (Lipsey and Sjöholm, 2004;Mah, 2002;Velde, 2003;Aitken, Harrison and Lipsey, 1996;Feenstra and Hanson, 1997).…”
mentioning
confidence: 97%
“…Thus, Tsai (1995), using a crosssection analysis for 53 economies, estimates a positive and significant relationship between fdi and inequality, although when he uses dummy control variables (Latin America and Asia) he finds that this positive relationship could be capturing differences in inequality between economies rather than any role played by fdi. Choi (2006), using a panel of 119 countries in the 1993-2003 period, finds evidence that an increase in fdi increases inequality. A similar finding is indicated by the work of Basu and Guariglia (2007), who, using a panel of 119 developing economies for the 1970-1999 period, report a positive relationship between fdi, economic growth, income inequality and human capital.…”
Section: Foreign Direct Investment (Fdi) and Income Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Choi (2006) reports an increase in income inequality with increasing FDI intensity using different proxies. Herzer et al (2014) establish a positive relationship between FDI and income inequality for Latin American countries.…”
Section: Foreign Direct Investment (Fdi)-income Inequalitymentioning
confidence: 99%
“…Hoi and Pomfret [34], Mah [35] and Choi [36] find that FDI increase country's income gap. Similarly, Figini and Goerg [17] claim that there is "a nonlinear effect in developing countries: wage inequality increases with FDI inward stock, with such effect diminishing with further increases in FDI."…”
Section: Literature Reviewmentioning
confidence: 99%